THE EFFECT OF AUDIT COMMITTEE EFFECTIVENESS ON CORPORATE PERFORMANCE OF SHARIA-COMPLIANT COMPANIES IN INDONESIA - Roghiebah Jadwa Faradisi (Universitas Darussalam Gontor, 2020)
This research aims to examine the effect of Audit Committee Effectiveness on corporate performance of sharia-compliant companies. We score this effectiveness using the activity, competency, size and independence of the Audit Committee, while Tobin’s Q is used to measure corporate performance of sharia-compliant companies. The sample for this study is 63 Sharia manufacturing companies listed on the Indonesia Stock Exchange and on the Sharia Stock List released by the Indonesia Financial Services Authority from 2014 to 2015. Using multiple regression, the results show that Audit Committee effectiveness has positive effect on corporate performance of sharia-compliant companies. Based on this result, Sharia companies should increase the effectiveness of their Audit committee, as it is used by investors to make investment decisions.